Clinico-Pathological Evaluation of Babesia gibsoni AssociatedRenal Failure in Dogs - Vidhya, Munagala Sree; Chandrasekar, M; Arunkumar, S; Subapriya, S; Sathish, G (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted to investigate clinical, hematological, and biochemical alterations in dogs infected with Babesia gibsoni, specifically associated with renal complications. Blood samples were obtained from 44 dogs exhibiting symptoms such as fever, lymph node enlargement, and reduced urine output. Babesia piroplasms were detected in 5 cases through blood smear examination, while PCR confirmed 10 positive cases. The dogs that tested positive for B. gibsoni underwent a comprehensive hematological and biochemical analysis to assess the severity of their condition. The primary hematological abnormalities observed were anemia and thrombocytopenia. Furthermore, the serum biochemical analysis revealed elevated levels of blood urea nitrogen (BUN) and creatinine, indicating renal insufficiency. During post mortem examination, a capsule firmly adhered to the kidney was seen macroscopically and histopathological analysis revealed renal tubular dilatation and presence of renal fibrosis. In the chronic stage of the disease, despite the absence of antigen replication within the host's body, the initiated inflammatory response can result in damage to multiple body systems. Therefore, it is of utmost importance to assess the disease's advancement and the overall condition of the animal.
Keywords: Babesia gibsoni; Biochemistry; Haematology; Histopathology; PCR